Закат и гибель Белого флота, 1918-1924 годы - Гончаренко Олег Геннадьевич (Военные тайны России, 2006)
Экземпляры: КХ (20070524) / Инвентарный номер: 1063281 / Цена: / Сис.шифр: 68.5/7 / Авт.знак: Г 65 / ГРНТИ: 78 / ББК: 68.53